Bisphosphonate therapy for thalassemia-related bone disorders in children and young adults: a systematic review - Ghea Mangkuliguna; I. Wayan Andrew Handisurya; Nicholas Adrianto (Annals of Pediatric Endocrinology & Metabolism, 2026)
Skeletal complications represent a major morbidity in transfusion-dependent thalassemia (TDT), particularly among children and young adults. Osteopenia and osteoporosis arise from marrow expansion, iron overload, endocrine dysfunction, and vitamin D deficiency, leading to impaired bone mass accrual. Although bisphosphonates are widely used in osteoporosis, their role in thalassemia has not been systematically appraised. This review aims to evaluate the role of bisphosphonates in pediatric and young adult patients with TDT-related bone disorders. A systematic search of PubMed/MEDLINE, Scopus, Cochrane Library, ProQuest, and gray literature was conducted from inception to August 2025. Eligible studies included randomized, nonrandomized, and prospective observational trials evaluating bisphosphonates in patients ≤25 years with TDT-related osteopenia or osteoporosis. Primary outcomes were changes in lumbar spine and hip bone mineral density (BMD). Secondary outcomes included biochemical markers, bone pain, fracture incidence, and safety. The review followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) 2020 guidelines and was registered in PROSPERO (CRD420251138498). Eleven nonrandomized prospective studies involving over 300 participants were included. Six studies evaluated pamidronate, 3 zoledronate, and 2 alendronate. Pamidronate generally improved lumbar spine and hip BMD, with more consistent gains when combined with calcium/vitamin D. Zoledronate was associated with BMD improvement but required pediatric-adjusted dosing to avoid hypocalcemia. Alendronate improved BMD z-scores and reduced bone pain in adolescents. Across studies, bisphosphonates lowered bone turnover markers and were generally well tolerated. Bisphosphonates may improve bone density and alleviate pain in TDT-related bone disease. Larger randomized controlled trials are required to determine long-term efficacy, fracture outcomes, and optimal treatment regimens.